Knowledge from Scientific Expert Testimony without Epistemic Trust - Leefmann, Jon; Lesle, Steffen (Synthese, 2018)
In this paper we address the question of how it can be possible for a non-expert to acquire justified true belief from expert testimony. We discuss reductionism and epistemic trust as theoretical approaches to answer this question and present a novel solution that avoids major problems of both theoretical options: Performative Expert Testimony (PET). PET draws on a functional account of expertise insofar as it takes the expert’s visibility as a good informant capable to satisfy informational needs as equally important as her specific skills and knowledge. We explain how PET generates justification for testimonial belief, which is at once assessable for non-experts and maintains the division of epistemic labor between them and the experts. Thereafter we defend PET against two objections. First, we point out that the non-expert’s interest in acquiring widely assertable true beliefs and the expert’s interest in maintaining her status as a good informant counterbalances the relativist account of justification at work in PET. Second, we show that with regard to the interests at work in testimonial exchanges between experts and non-experts, PET yields a better explanation of knowledge-acquisition from expert testimony than externalist accounts of justification such as reliabilism. As our arguments ground in a conception of knowledge, which conceives of belief-justification as a declarative speech act, throughout the rearmost sections of this paper we also indicate to how such a conception is operationalized in PET.<br
Keywords: Expert knowledge; Performative testimony; Epistemic justification; Assertability; Epistemic community

Peter Baumann: Epistemic Contextualism.A Defense, 255 S., Oxford University Press, Oxford 2016. - Lesle, Steffen (2017)

Stephen Hetherington: Knowledge and the Gettier Problem, 253 S., Cambridge University Press, Cambridge 2016. - Lesle, Steffen (2018)